Pelatihan Berbalas Pantun Siswa SD Negeri 005 Bukit Ranah - Nur, Hidayatun; Sukenti, Desi; Latif, Latif; Hermaliza, Hermaliza; Mukhlis, Muhammad; Fahmi, Dicky; Lestari, Diyah Ayu (UIR Press, 2025)
This article aims to describe the training activities for berbalas pantun to students' at SDN 005 Bukit Ranah. Elementary School 005 Bukit Ranah is a public school located on Jalan Pekanbaru-Bangkinang, Kampar Regency, Riau Province. The majority of students at Elementary School 005 Bukit Ranah are of Malay ethnicity and culture. Almost all of the students use the local Malay language with the Kampar Malay dialect. As a Malay-based school, this school needs training in pantun reciprocation because the school is looking for students who are talented in pantun reciprocation. Training on writing pantun has been carried out but the activity did not focus on practicing pantun reciprocation even though the school needs talented students to take part in pantun reciprocation competitions. This training activity is carried out using lecture and practice methods. By holding pantun reciprocation training, students can later develop their talents and become representatives for pantun reciprocation competitions. This activity was attended by 25 members taken from representatives of classes 1-6. After participating in the training, a picture of participants who have talent in pantun reciprocation can be obtained by paying attention to the pantun reciprocation aspect.